Emotional awareness, emotional self- regulation and empathy among the working adolescents - Shilpa Das; Dr. Akash Mahato; Dr. Susmita Halder (International Journal of Indian Psychȯlogy, 2022)
Background: Empathy, Emotional- awareness and Emotional self –regulation are important domains of emotional intelligence (EI). These are significant factors to handle any relationship. Empathy helps adolescents to comprehend the feelings of others and to communicate appropriately. Emotional awareness helps to understand what others are communicating to them and reason behind it. Emotional self-regulation improves the performance at work, enrich personal relationship and also enhance betterment of mood. In the long run, these three aspects increase compassion and feelings for others. Special features of working in adolescence need to be taken into account in considering its consequences for development during this phase of life. Work by young people tends to be more discretionary that interferes with the proper growth and development of them in all aspects like mentally, physically, socially and intellectually. Objective: The aim of this study is to find out whether is there any difference in emotional awareness, emotional self-regulation and empathy between non-working and working adolescents. Method: 60 male adolescents (30- non- working and 30 working), aged between 13 to 17 years were included in the study and assessed levels of empathy, emotional awareness and emotional self-regulation. Self-report measures namely empathy questionnaire for children and adolescents (Emque-ca), emotional awareness questionnaire (Eaq) and the emotion regulation questionnaire for children and adolescents (Erq-ca) were used. Result: The study suggests significant difference between the groups in empathy, emotional awareness and emotional self-regulation. Conclusion: It can be concluded that in working adolescents having difficulty in emotional awareness, emotional self –regulation, and empathy.